ON QUASI-RECTANGULAR BANDS - AMINPOUR, M. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper we present a new definition of quasi-semigroups and quasi-rectangular bands, principal result Â are that every quasi-rectangular band Â is isomorphic to the Â direct Â product of a quasi-left zero semigroup and Â quasi-right zero semigroup Â [theorem Â 3.5]. Mathematical Society Classification: 2010 MSC. 18340. KeyÂ Â wordsÂ Â andÂ Â phrases. Â Quasi-product, quasi-semigroup,Â Â quasi-rectangularÂ Â band, quasi-left zero semigroup. Â